KEBIJAKAN TARIF IMPOR PAHA AYAM DALAM MELINDUNGI INDUSTRI PERUNGGASAN NASIONAL - SIREGAR, MASDJIDIN; RUSASTRA, I WAYAN (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 3, No. 2 Juli 2003, 2012)
The objectives of this paper are to analyze the competitiveness and comparative advantage of broiler production and to recommend alternative policies on import tariff and non-import tariff barriers for chicken leg-quarter (CLQ), aimed at protecting the national broiler industry. The results of the analysis indicate that Indonesia has the comparative advantage of whole chicken, but not in the form of parting chicken, particularly CLQ. Under an assumption that the profit of broiler industry is at least 20 percent of the total broiler production costs, the import tariff rate for CLQ should be 100 percent of CIF value of US$ 630/ton. Should the profit be 25 percent and 30 percent of the total broiler production costs, the fair tariff rates would be 110 percent and 120 percent. Such an import tariff policy for CLQ should be complemented by several strategic non-tariff policies, i.e.: (i) ASUH policy (save, healthy, whole and halal) which is considered comprehensive and effective; (ii) overall review on the implementation of halal conditions in USA; (iii) import quantity barrier for CLQ as raw material for processed meat industry; (iv) smuggling abolition and law enforcement as the consequences of a high import tariff implementation; and (v) for the urgency and the economic viability of the national broiler industry, it is essential to carry out political lobby to limit or even to stop CLQ export from USA to Indonesia.
Keywords: Competitiveness and Comparative Advantage, Policies on Import Tariff, Policies on Import Tariff, National Broiler Industry